Greenland, view of Kjerulf Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 1, 1931. Kjerulfs [Kjerulf] Fjord. Extreme inner end. In foreground on left southern terminal of mountains forming eastern side Kjerulfs [Kjerulf] Fjord. In background on right L.A.B.'s Scoop Mt. [Mountain] In foreground stream of Right Valley. Photo taken from triangular junction of Left, Right, and Main Valleys looking S.E.